#InstaMind: teachers’ beliefs on educational technology to promote seamless technology integration in early education - Peretti, Sara; Kubiatko, Milan; Caruso, Federica; Di Mascio, Tania; Giancola, Marco; D’Amico, Simonetta; Pino, Maria Chiara (Frontiers in Education, 2024)
Background: The digital revolution has deeply affected every aspect of our daily lives, including education, transforming how we learn and teach. In Italy, this transformation has occurred naturally for the alpha generation, born in the era in which technology is an integral part of their education. Conversely, for teachers who are not digital natives, adapting to this technological era is a considerable challenge. This challenge is increasing for Italian teachers working with preschoolers. Indeed, prior to the COVID-19 pandemic, such technologies were sparsely utilized within early education. This study aims to explore Italian teachers' beliefs through internal factors—i.e., self-efficacy, outcome expectations, and interest, towards the integration of educational technology in teaching. Methods: To this end, the standardized Intrapersonal Technology Integration Scale was selected to measure the Italian teachers' beliefs. The study includes 180 teachers working with the alpha generation, which encompasses children currently attending pre-kindergarten, kindergarten, and primary education. Results: The results obtained from the comparison among the three groups of teachers (pre-kindergarten, kindergarten, and primary education) on the internal factors are manifold. Mainly, although all teachers are interested in educational technologies, there is a reluctance and low self-efficacy perception to use them with preschoolers. Specifically, pre-kindergarten teachers perceive themselves as less effective and satisfied using such technologies than kindergarten and primary teachers. Moreover, greater teachers' age and greater teaching experience predict a lower level of perceived self-efficacy and outcome expectations, highlighting resistance towards technological change. All results and their implications are detailed in this text. Discussion: This study suggests focusing on perceived self-efficacy, offering customized training to enhance it, exploiting the teachers’ interest, enriching teachers' knowledge through scientific dissemination seminars, and using an effective method. To conclude, understanding teachers' beliefs is a challenge to better meet the needs of the digital-native generation and harness the potential of educational technologies in childhood education.